MENINGKATKAN HARDINESS TUNANETRA DENGAN TEKNIK COGNITIVE RESTRUCTURING DAN SELF-TALK - Sri Maullasari; Mungin Eddy Wibowo; Awalya Awalya (UIN Sunan Kalijaga Yogyakarta, 2021)
AbstractHardiness is a mental state to face challenges and difficulties. A person with a high level of hardiness can avoid stress. The purpose of this study was to analyze the effectiveness of group counselling on cognitive restructuring and self-talk in increasing the hardiness of the blind. In this study, the experimental design used was